Dissociations in semantic cognition: Oscillatory evidence for opposing effects of semantic control and type of semantic relation in anterior and posterior temporal cortex. (November 2019) - Teige, Catarina; Cornelissen, Piers L.; Mollo, Giovanna; Gonzalez Alam, Tirso Rene del Jesus; McCarty, Kristofor; Smallwood, Jonathan; Jefferies, Elizabeth
Abstract: How does the brain represent and process different types of knowledge? The Dual Hub account postulates that anterior temporal lobes (ATL) support taxonomic relationships based on shared physical features (mole – cat), while temporoparietal regions, including posterior middle temporal gyrus (pMTG), support thematic associations (mole – earth). Conversely, the Controlled Semantic Cognition account proposes that ATL supports both aspects of knowledge, while left pMTG contributes to controlled retrieval. This study used magnetoencephalography to test these contrasting predictions of functional dissociations within the temporal lobe. ATL and pMTG responded more strongly to taxonomic and thematic trials respectively, matched for behavioural performance, in line with predictions of the Dual Hub account. In addition, ATL showed a greater response to strong than weak thematic associations, while pMTG showed the opposite pattern, supporting a key prediction of the Controlled Semantic Cognition account. ATL showed a stronger response for word pairs that were more semantically coherent, either because they shared physical features (in taxonomic trials) or a strong thematic association. These effects largely coincided in time and frequency (although an early oscillatory response in ATL was specific to taxonomic trials). In contrast, pMTG showed non-overlapping effects of semantic control demands and thematic judgements: this site showed a larger oscillatory response to weak associations, when ongoing retrieval needed to be shaped to suit the task demands, and also a larger response to thematic judgements contrasted with taxonomic trials (which was reduced but not eliminated when the thematic trials were easier). Consequently, time-sensitive neuroimaging supports a complex pattern of functional dissociations within the left temporal lobe, which reflects both coherence versus control and distinctive oscillatory responses for taxonomic overlap (in ATL) and thematic relations (in pMTG).